Bit-error rate performance analysis of spectrum based detector for FSK digital modulation - Sha'ameri, Ahmad Zuri (2003)
FSK is widely used digital modulation technique due to its simplicity in implementation using noncoherent detection. Further availability of digital signal processing algorithms such as the FFT (Fast Fourier Transform) and necessary supporting technology makes it possible to implement spectrum based deteetor for FSK. This paper formulates the BER (Biterror rate) performance of the spectrum based detector. Generally, the performance lies between the optimum that is. the coherent detector and the suboptimum that is the noncoherent detector. Verification was performed by computer simulation to confirm the results.